Teori Modern Sosiologi Pendidikan : Analisis Implementasi Pada 5 Sekolah di Kutai Timur - Reva Annisa; Sriwahyuni Tamher; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This study analyzes the implementation of Modern Theory of Sociology of Education, including the concepts of cultural reproduction (Bourdieu), social capital (Coleman), and resistance (Willis) in five representative secondary education institutions in East Kutai Regency: SMAN 1, SMAN 2, SMKN 1, SMKN 2, and MA Nurul Hikmah. This qualitative, multiple case study study found that schools operate as complex arenas of social reproduction. This reproduction mechanism is manifested through a hidden curriculum that unconsciously validates the academic cultural capital possessed by students from middle-class backgrounds, while students from working-class families tend to experience alienation and marginalization. In vocational schools, social capital, as measured by the local school-industry partnership network, is a key determinant of graduate success, effectively replicating occupational stratification. However, the findings also identify pedagogical resistance and bottom-up initiatives by teachers and school management to build collective social capital, particularly at MA Nurul Hikmah through the strengthening of religious symbolic capital. This analysis highlights that centralized education policies tend to reinforce stratification between schools amidst local resource disparities. This research recommends the need for more substantive curriculum decentralization and progressive resource allocation to transform schools into agents of social mobility that are inclusive and responsive to the specific socio-economic dynamics in East Kutai.